2016
DOI: 10.1139/cgj-2015-0126
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of unstable rock failure under unloading conditions

Abstract: Rockburst is an unstable rock failure and one of the most hazardous problems in deep hard-rock mines. Before excavation, rocks are loaded under a polyaxial condition. Upon excavation, the rocks at the excavation boundaries are loaded in the tangential direction and unloaded in the radial direction. Understanding rock behaviour under this excavation loading condition is critical for developing measures to control rock failure in underground construction. In this paper, numerical simulation results of unstable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…2D numerical modeling results using the Discrete Element Method found that the post-peak stress-strain curve of rock under the critical loading condition was close to that under a rigid loading condition (LSS = ∞) (Kias and Ozbay 2013). This observation was confirmed by Manouchehrian and Cai (2015) using a 3D Finite Element Method (FEM) numerical model.…”
Section: Energy Transfer Energy Transfer Energy Transfermentioning
confidence: 58%
See 4 more Smart Citations
“…2D numerical modeling results using the Discrete Element Method found that the post-peak stress-strain curve of rock under the critical loading condition was close to that under a rigid loading condition (LSS = ∞) (Kias and Ozbay 2013). This observation was confirmed by Manouchehrian and Cai (2015) using a 3D Finite Element Method (FEM) numerical model.…”
Section: Energy Transfer Energy Transfer Energy Transfermentioning
confidence: 58%
“…However, ∆E in was not excluded in previous numerical models (Hemami and Fakhimi 2014;Kias and Ozbay 2013;Manouchehrian and Cai 2015) and the rock failure processes observed were the product of ∆E t plus ∆E in . If ∆E in is provided during the rock failure process, the rock failure type under the loading condition of LSS > λ depends upon the amount of ∆E in .…”
Section: Energy Transfer Energy Transfer Energy Transfermentioning
confidence: 99%
See 3 more Smart Citations